Impoliteness Strategies Used In Dailymail's Comments - Yulidar, Luthfi, Agus Wijayanto, Ph.D, Mauly Halwat Hikmat, Ph.D (2017)
This research investigated impoliteness strategies used in Dailymail's comments. It is qualitative research. The objectives of this research are describing the types of impoliteness strategies found dominantly and the conventional form of impoliteness in Dailymail's comments. The data are the comments of Dailymail site. The researcher uses documentation method to collect the data, by doing some steps: reading and understanding the comments below the article, writing the data of impoliteness strategies found in the comments, and coding. The data were analyzed by the theory of impoliteness by Culpeper (2005) and conventional form of Culpeper's theory (2010). There are 3 steps in analyzing the data, as follow: analyzing the impoliteness strategies in Dailymail's comments, analyzing the conventional form of impoliteness, and drawing conclusion. The finding of this research shows that not all the impoliteness strategies found in this research. There are bald on record impoliteness, positive impoliteness, negative impoliteness, and offrecord impoliteness or sarcasm/mock impoliteness and pragmalinguistic of impoliteness strategies can be expressed with some form, such assessing, figurative language, rhetorical question, telling the truth, giving advice, etc.